(untitled) - Kovacs, Karen (Thành phố Hồ Chí Minh, 2012)
The book is devided into 12 units. Each unit focuses on a topic area that you are likely to meet in the IELTS exam
Keywords: English language,Tiếng Anh; Examinations, questions, etc,Kỳ thi, câu hỏi, vv